“REDESAIN PASAR UNIT KOTA BOJONEGORO” - Meinanda Rizal Rodyanto; Maya Andria Nirawati; Ana Hardiana (ARSITEKTURA, 2016)
Along with the times, there is a change in consumer demands and standards on traditional markets so that traditional market currently being replaced by the modern market. The phenomena appeared in Bojonegoro, condition of traditional market not comply the standards of market, the market that become focus is the small-scale market of Bojonegoro because the potential of the small-scale market of Bojonegoro still need to be explored with the correct market managemet and innovation to form the image of traditional market that are able to comply consumer standard. Design issues are: how the concept of redesigning The small-scale market of Bojonegoro in accordance with the evaluation results after occupancy in the previous unit. Redesign method of the small-scale market of Bojonegoro that is with stage of observation after occupancy as a reference in consideration of planing and design to redisgn the small-scale market of Bojonegoro The result obtained is a design of a The small-scale market of Bojonegoro based on occupancy evaluation on the previous unit market.Keyword : Post Occupancy Evaluation (POE), Redesign Market,Tradisional Market, The Small-Scale Market of Bojonegoro.Along with the times, there is a change in consumer demands and standards on traditional markets so that traditional market currently being replaced by the modern market. The phenomena appeared in Bojonegoro, condition of traditional market not comply the standards of market, the market that become focus is the small-scale market of Bojonegoro because the potential of the small-scale market of Bojonegoro still need to be explored with the correct market managemet and innovation to form the image of traditional market that are able to comply consumer standard. Design issues are: how the concept of redesigning The small-scale market of Bojonegoro in accordance with the evaluation results after occupancy in the previous unit. Redesign method of the small-scale market of Bojonegoro that is with stage of observation after occupancy as a reference in consideration of planing and design to redisgn the small-scale market of Bojonegoro The result obtained is a design of a The small-scale market of Bojonegorobased on occupancy evaluation on the previous unit market. Keyword : Post Occupancy Evaluation (POE), Redesign Market,Tradisional Market, The Small-Scale Market of Bojonegoro.